An unusually compact ribosomal DNA repeat in the protozoan Giardia lamblia. - Boothroyd, J C (1987)
The ribosomal RNA (rRNA) genes of the protozoan parasite Giardia lamblia have been analyzed with respect to size, composition and copy number. They are found to be remarkable in several respects. First, the rRNAs themselves are the smallest yet reported for any eukaryotic organism. Second, the genes encoding them are found as an exceptionally small tandemly repeated unit of only 5.4 kilobase-pairs. Third, the genes are extraordinarily G:C rich, even in regions which are highly conserved between all other eukaryotic rRNA genes. Finally, by analogy to other organisms, the 5.8S RNA appears to lack about 15 nucleotides from its 3'-end, a region previously thought to be essential for 5.8S RNA function. We also provide the first estimates of the genomic complexity and total G:C content of this important protozoan pathogen.